Pericytes at the intersection between tissue regeneration and pathology - Birbrair, Alexander (2015)
Perivascular multipotent cells, pericytes, contribute to the generation and repair of various tissues in response to injury. They are heterogeneous in their morphology, distribution, origin and markers, and elucidating their molecular and cellular differences may inform novel treatments for disorders in which tissue regeneration is either impaired or excessive. Moreover, these discoveries offer novel cellular targets for therapeutic approaches to many diseases. This review discusses recent studies that support the concept that pericyte subtypes play a distinctive role in myogenesis, neurogenesis, adipogenesis, fibrogenesis and angiogenesis.